Abeni's song - Clark, P. Djèlí (Clark, P. Djèlí. Abeni's song, 2023)
Abeni, a reluctant magical apprentice, and a team of spirit kids set out to save their village from the evil Witch Priest who captured and marched off everyone toward ghost ships bound for distant lands.